Analisis Pengaruh Penerapan Prinsip-Prinsip Good Governance Terhadap Pelayanan Publik Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Mimika - Juandi Pademme Patiung; Spedy Paereng (STIE Jambatan Bulan, 2022)
This study aims to determine the effect of applying the principles of Good Governance to public services at the Mimika Regency Population and Civil Registration Service. To answer the formulation of the first and second problems using descriptive methods, where descriptive methods are used to describe or analyze research data but not to draw broader conclusions on population characteristics. To answer the third problem formulation using associative research methods, where associative research methods are used to determine the effect of one or more independent variables (independent) on one dependent variable. In this study, the data collection techniques used were questionnaires, interviews and observations. The results of this study indicate that the application of the principles of Good Governance and public services has already been implemented properly in the implementation of public services, but on the other hand it is different from the principle of justice which still has deviations so that the services provided are not yet fair to the community. And based on the test results on each indicator of Transparency, Responsiveness, Justice, it turned out that Good Governance had an influence in supporting the implementation of public services at the Population and Civil Registration Office in Mimika Regency.